STUDI TRANSPOR SEDIMEN DI PERAIRAN PANTAI KALIMANTAN TIMUR DENGAN MENGGUNAKAN MODEL HIDRODINAMIKA - Prasetiyo, An’am; Yusuf, Mustaid; Mislan, Mislan (GEOSAINS KUTAI BASIN, 2019)
The study was conducted in Balikpapan Bay, Adang Bay, and Apar Bay to simulate sediment transport induced by tidal current. The sediment transport information is very important for environmental management as well as environmental impact analysis. This study has applied COHERENS (Coupled Hydrodynamical Ecological model for Regional and Shelf Seas). Barotropic mode of COHERENS has performed the simulation from 15 December 2012 to 14 January 2013, using 8 tidal component delivered from NAO99b as generation force. The model simulation result are verified using tides of observation data from 15 December to 31 December 2012 the Semayang Port. Verification result shows a good agreement between simulation data and observation. The RMSE is about 0.158 meter. In Balikpapan Bay the result shows higher concentration points is are located at Port area and Riko River Estuary, with sediment transport around 1.1577 x10-4 (kg/m2)/s, on Adang Bay the concentration point is located at inner part of Bay, with transport sediment around 1.6499 x10-4 (kg/m2)/s, and at Apar Bay concentration point is located at outer part of Bay, with sediment transport value around x10-15 (kg/m2)/s.